PENGEMBANGAN MODEL PEMBELAJARAN UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA - Isop Syafei (Fakultas Psikologi, Universitas Islam Negeri (UIN) Sunan Gunung Djati Bandung, 2015)
This study was motivated by the fact that the process of learning the Quran Hadith subject in Madrasah Aliyah is still far from developing the students' critical thinking skills, caused by the learning process most focused on result and value (product oriented). This study aimed to generate and develop a learning model to improve student’s critical thinking skills. This research was conducted using research and development approach (R & D), included (1) a preliminary study, (2) Model Development, and (3) Test validation. Model testing carried out by experiment in the form of a quasi-experimental design with pretest-posttest control group design. The results showed that the learning model developed proved more effective to improve the processes and outcomes of learning the Qur'an Hadith. In terms of the learning process, the implementation of this model can improve the performance of teachers, namely; more effective learning time, learning more concentrated and more controlled learning activities.